2006
DOI: 10.1115/1.2386164
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Forging Using Electrical Flow as an Alternative to Warm/Hot Working

Abstract: Manufacturing processes (e.g., forging, rolling, extrusion, and forming) rely on heat to reduce the forces associated with fabricating parts. However, due to the negative implications associated with hot working, another more efficient means of applying energy is desired. This paper investigates material property changes of various metals (aluminum, copper, iron, and titanium based alloys) in response to the flow of electricity. Theory involving electromigration and electroplasticity is examined and the implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
90
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 9 publications
10
90
1
1
Order By: Relevance
“…As recently reported by Ross et al 14 and Perkins et al, 15 the presence of a continuous electric current during plastic deformation of a metal may significantly reduce the flow stress of the metal. Under compression, the formability of a metal is significantly enhanced with application of a continuous electric current.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…As recently reported by Ross et al 14 and Perkins et al, 15 the presence of a continuous electric current during plastic deformation of a metal may significantly reduce the flow stress of the metal. Under compression, the formability of a metal is significantly enhanced with application of a continuous electric current.…”
mentioning
confidence: 51%
“…3. Perkins et al 15 reported the results for various materials investigated in electrically-assisted compression tests such as 304 stainless steel, 360 brass, and 6061 T6511 aluminum alloys. The contribution of electroplasticity of these materials decreased the total required energy versus current density.…”
Section: Compression Testmentioning
confidence: 99%
See 2 more Smart Citations
“…• Threshold versus resistivity relation [22] • Dislocation density versus temperature relation (stationary-electrical tests) [4] • Springback elimination in sheet bending [23] • Dislocation density versus EEC (EAF tests) [4] Experimental work supports the theory of localized resistive heating due to the applied electricity. From this previous work, a threshold current density value has become apparent which is specific to each metal tested [22].…”
Section: Heating and Increased Atomic-level Vibrationsmentioning
confidence: 96%